High-intensity Interval Training Improves Lipocalin-2 and Omentin-1 Levels in Men with Obesity - Atashak, Sirvan; Stannard, Stephen R.; Daraei, Ali; Soltani, Mohammad; Saeidi, Ayoub; Moradi, Fatah; Laher, Ismail; Hackney, Anthony C.; Zouhal, Hassane (International Journal of Sports Medicine, 2021)
We investigated the effects of 12 weeks of high-intensity interval training (HIIT) on selected circulating adipokines and other cardiovascular diseases risks factors in men with obesity. Thirty men with obesity (age: 24.96±3.11 year, BMI: 30.92±1.04 kg/m2) were randomly assigned to HIIT and control groups. The HIIT group participated in a 12-week HIIT program (5×2 min interval bout at an intensity of 85–95% HRmax interspersed by 1 min passive recovery, three times per week), while the control group maintained their usual lifestyles. Blood lipids, insulin resistance, and select serum adipokines were assessed before and after 12 weeks of the intervention period. HIIT improved body composition and lipid profiles (p<0.05) and also decreased fasting insulin levels (p=0.001) and HOMA-IR (p=0.002) levels. Furthermore, HIIT increased levels of lipocalin-2 (p=0.002) while decreasing omentin-1 levels (p=0.001) in men with obesity. Changes in lcn2 and omentin-1 concentrations correlated with the changes in risk factors in the HIIT group (p<0.05). The results indicate that 12 weeks of supervised HIIT significantly improves both circulating concentrations of lcn2 and omentin-1, two recently described adipokines, and risk markers of cardiovascular diseases in men with obesity. Further research is necessary to understand the molecular mechanisms involved with these changes.
Keywords: HIIT; lipid profile; body composition; insulin resistance